2009
DOI: 10.1111/j.1469-0691.2009.02747.x
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation by Propionibacterium acnes is a characteristic of invasive isolates

Abstract: Propionibacterium acnes is a common and probably underestimated cause of delayed joint prosthesis infection. Bacterial biofilm formation is central in the pathogenesis of infections related to foreign material, and P. acnes has been shown to form biofilm both in vitro and in vivo. Here, biofilm formation by 93 P. acnes isolates, either from invasive infections (n = 45) or from the skin of healthy people (n = 48), was analysed. The majority of isolates from deep infections produced biofilm in a microtitre model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
136
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(150 citation statements)
references
References 27 publications
7
136
1
1
Order By: Relevance
“…The matrix confers resistance to penetration of antibiotics through the biofilm into the microbes [5,6]. Classically, biofilms were considered to be primarily associated with catheter or implant-associated infections, as well as dental plaques [7]. The earlier years of research had clearly demonstrated the formation of P. acnes forming biofilms in vitro and on medical appliances, but it had yet to be discovered as a biofilm within the follicle itself [8].…”
Section: Biofilm Formation Of P Acnesmentioning
confidence: 99%
“…The matrix confers resistance to penetration of antibiotics through the biofilm into the microbes [5,6]. Classically, biofilms were considered to be primarily associated with catheter or implant-associated infections, as well as dental plaques [7]. The earlier years of research had clearly demonstrated the formation of P. acnes forming biofilms in vitro and on medical appliances, but it had yet to be discovered as a biofilm within the follicle itself [8].…”
Section: Biofilm Formation Of P Acnesmentioning
confidence: 99%
“…[131] Biofilms of Propionibacterium acnes bacteria have been found to be considerably inactivated by two types of plasma jet over short time periods. [121] Biofilms of MRSA, Staphylococcus epidermidis, Staphylococcus aureus and Escherichia coli are also removed by CAP treatment.…”
Section: Tbtm Contaminants Such As the Anaerobic Gram-positive Propiomentioning
confidence: 99%
“…To date, a number of phenotypic and/or molecular approaches have been investigated as methods for phylogroup identification, ranging from very simple biochemical tests based on hemolysis (19) or fermentation profiles (40) to matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) (41), monoclonal antibody (MAb) typing (18), and DNAbased analysis; DNA-based analysis includes ribotyping (23), DiversiLab analysis (42), direct PCR assays (43), and protein-coding gene sequencing (18,20,21,44). Unfortunately, many of these approaches suffer from specificity or sensitivity limitations that constrain their diagnostic value.…”
mentioning
confidence: 99%